#JagaAirKita in the Digital Era: A Study of an Environmental Campaign on Instagram - Permatasari, Annisa; Hafiz, Aliya Ramdhani; Candra, John William (Communicare : Journal of Communication Studies, 2025)
Jakarta, Indonesia’s capital, faces intertwined crises of land subsidence, sea level rise, and water pollution, making it a crucial context for crisis communication. The DKI Jakarta Water Resources Agency launched the #JagaAirKita (“Let’s Protect Our Water”) campaign via Instagram (@sobatair.jkt) to raise public awareness and engagement. This qualitative case study analyzes the campaign using Aristotle’s rhetorical appeals ethos, pathos, logos and dialogic theory. Findings show the campaign employs a dual ethos: projecting state authority while positioning itself as a relatable community ally. Pathos is effectively used through emotive storytelling that connects with youth audiences. However, its challenge with logos, particularly in presenting technical data, reflects reliance on the knowledge-deficit model, which assumes information alone changes behavior. From a dialogic perspective, the campaign blends online and offline activities, showing potential for two-way engagement, yet remains largely top-down. While it fosters awareness, it has not fully embraced collaborative, community-centered approaches that empower public participation. This study offers insights into environmental communication and digital governance in climate-vulnerable megacities, suggesting a strategic shift from purely informational methods toward relational, dialogic engagement to build sustained public involvement in addressing water-related environmental risks.